Implementasi Hukum Tentang Perjanjian Gadai Tanah Pertanian Di Desa Pilohayanga Kecematan Telaga Kabupaten Gorontalo - Yunus, Yultiar Rahmat; Junus, Nirwan; Mandjo, Julius T. (CV. ITTC INDONESIA, 2022)
The pawning of agricultural land is basically a transaction regarding land that is used as an object in collateral for debt between the land owner or the mortgagee and the pawn recipient with the aim of obtaining capital by not selling the land that is used as the object in the mortgage of the agricultural land, so the mortgage on agricultural land has the right redeem to get agricultural land that has been mortgaged to the recipient of the pawned agricultural land. The purpose of this study was to examine the implementation of the pawn agreement in Pilohayanga Village, Telaga District, Goronntalo Regency and the legal consequences of the pawn agreement on agricultural land after the pawn period ended based on Perpu no.56 of 1960 and the obstacles in implementing the pawn agreement on agricultural land in Pilohayanga Village, Telaga District, Gorontalo Regency The research conducted was empirical normative legal research with a sociological juridical approach taken from primary data by conducting interviews and secondary data by processing data from primary legal materials, secondary legal materials. This happens because the people in Pilohayanga Village, who are generally village people, more often use customary law or verbal agreements in implementing agricultural land mortgage agreements because they are considered more efficient and easier to implement. So that the role of the government and the community is needed so that land pawn regulations can be effectively applied, especially in Pilohayanga Village.